Structural and Functional Analyses of Type I IFNa Shed Light Into Its Interaction With Multiple Receptors in Fish - Wang, Zixuan; Xu, Jing; Feng, Jianhua; Wu, Kaizheng; Chen, Kangyong; Jia, Zhao; Zhu, Xiaozhen; Huang, Wenji; Zhao, Xin; Liu, Qin; Wang, Bangjie; Chen, Xinhua; et al. (Frontiers in Immunology, 2022)
Teleost type I interferons (IFNs) are categorized into group I and II subgroups which bind to distinct receptors to activate antiviral response. However, the interaction between IFN ligands with receptors has not fully been understood. In this study, the crystal structure of grass carp (Ctenopharyngodon idella, Ci) IFNa has been solved at 1.58Å and consists of six helices. The CiIFNa displays typical structure of type I IFNs with a straight helix F and lacks helix element in the AB loop. Superposition modeling identified several key residues involved in the interaction with receptors. It was found that tCiIFNa bound to CRFB1, CRFB2 and CRFB5 and the three receptors could form paired receptor complex. Further, Mutation of Leu27, Glu103, Lys117 and His165 markedly decreased the phosphorylation of STAT1a induced by CiIFNa in the EPC cells and Glu103 was shown to be required for the CiIFNa activated antiviral activity. Interestingly, wildtype and mutant CiIFNa proteins did not alter the phosphorylation levels of STAT1b. Our results demonstrate that fish type I IFNs, although structurally conserved, interact with the receptors in a manner that may differ from mammalian homologs.